Interrupted Innocence: The protection of fundamental rights of children and adolescents in relation to VRAEM case - Rebaza Vilchez, Karen Maribel (2014)
In this article the author identifies - from a international law and constitutional perspective - the Block of Constitutionality concerning the protection of chíldren and adolescents víctíms of recruitment by rebel groups, in arder to sustain the need of promulgation of rules in the interna[ legal system to protect the rights of this vulnerable group and to avoid, at the same time, a possible imputation of international responsibility to the Peruvian State for failing with his respective international obligations.